Decolonizing Urban Political Ecologies: The Production of Nature in Settler Colonial Cities. Issue 2 (4th March 2018) - Simpson, Michael; Bagelman, Jen
Abstract : This article contributes to the decolonization of urban political ecology (UPE) by centering the ongoing processes of colonization and its resistances that produce urban natures in settler colonial cities. Placing the UPE literature in conversation with scholarship on settler colonialism and Indigenous resurgence, we demonstrate how the ecology of the settler colonial city is marked by the imposition of a colonial socionatural order on existing Indigenous socionatural systems. Examining the case of Lekwungen territory, commonly known as Victoria, British Columbia, we consider how parks, property lines, and settler agriculture are inscribed on a dynamic food system maintained by the Lekwungen over millennia. The erasure of the Lekwungen socioecological system, however, has never been complete. Efforts of the Lekwungen and their allies to continue managing these lands as part of an Indigenous food system have resulted in conflict with volunteer conservationists and parks officials who assert their own jurisdictional authority over the space. Drawing on interviews and participant observation research, we argue that the seemingly quotidian and everyday acts of tending to urban greenspace by these groups are actually of central importance to struggles over the reproduction of UPEs in the settler colonial city.